AiREAS: Sustainocracy for a Healthy City The Invisible made Visible Phase 1 - Close, Jean-Paul (SpringerBriefs on Case Studies of Sustainable Development, 2016)
This book describes the coming about and first results of the AiREAS "healthy city" cooperative in the city of Eindhoven and Province of North Brabant in the Netherlands. AiREAS is an initiative focused on the multidisciplinary co-creation of healthy cities using the core human value of human health and air quality as guiding principle for profound regional innovation. The unique group process that followed uses the complexity of the city of Eindhoven as living lab. It is an anthropology based initiative that invites directly to the same table of core innovative responsibility the local government, innovative business partners, scientific insights and reseach, and civilian participation. The first phase is described here in which the consortium decided to want to make the invisible of air pollution and human exposure visible for the integral innovative participation of all city's core pillars (policy, education, infrastructure, culture and entrepreneurship). The experience is unique in the world and proceding now with more phases in Eindhoven and the role out of the same working format in other cities. This Brief is made available to inspire the world to address together the most complex issues of our current era: pollution, climate and core human values. .